Proceedings of ‏The 6th International Conference on Opportunities and Challenges in Management, Economics and Accounting 2020
DOI: 10.33422/6th.omeaconf.2020.09.209
|View full text |Cite
|
Sign up to set email alerts
|

Technological Skills and Job Employment in Universities in Saudi Arabia

Abstract: Due to the rate of youth unemployment in Middle East precisely Saudi Arabia, this study investigates the relationship between technological skills and job employment among the unemployment youth in Saudi Arabia. Specifically, the study examined how technological related skills such as IT, computer skills and internet related skills predict job employment among the unemployed youths in Riyadh, Saudi Arabia. The study adopted a cross-sectional research design with quantitative questionnaire survey approach. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Higher education institutions (HEIs) need to be precisely aware about the expectations and requirements as expected by employers (Sin & Amaral, 2017). In addition, there are many studies that have investigated Gulf Cooperation Council (GCC) countries and Saudi Arabia, wherein the findings revealed that HEIs frequently accord low significance to transversal employability skills owing to imprecise views of suboptimal policies or the labour market (Ali Al-khateeb, 2020;Belwal et al, 2017;Griffin & Coelhoso, 2019). At the same time, employers offer significant insights into probable enhancements to academic curriculums owing to their role as a key factor that influences the labour market.…”
Section: Role Of Higher Education Institutions In Developing Employab...mentioning
confidence: 99%
See 1 more Smart Citation
“…Higher education institutions (HEIs) need to be precisely aware about the expectations and requirements as expected by employers (Sin & Amaral, 2017). In addition, there are many studies that have investigated Gulf Cooperation Council (GCC) countries and Saudi Arabia, wherein the findings revealed that HEIs frequently accord low significance to transversal employability skills owing to imprecise views of suboptimal policies or the labour market (Ali Al-khateeb, 2020;Belwal et al, 2017;Griffin & Coelhoso, 2019). At the same time, employers offer significant insights into probable enhancements to academic curriculums owing to their role as a key factor that influences the labour market.…”
Section: Role Of Higher Education Institutions In Developing Employab...mentioning
confidence: 99%
“…Given the framework of a knowledge economy that is continuously changing, this narrow focus on technological skills on the part of HEIs in Saudi adds on to the development of a skill gap that has a negative impact on the employment profile of the nation in particular, and the economy on the whole (Ebaid, 2021). This issue is further aggravated by certain economic barriers that needs redressal with due cooperation from main stakeholders (Ali Al-khateeb, 2020). The said challenges are multiplied owing to the fact that curriculums with HEI's in Saudi accord priority to humanities and these include religious and language studies, as compared to subjects that are highly in demand (Alghamedi, 2016).…”
Section: Role Of Higher Education Institutions In Developing Employab...mentioning
confidence: 99%
“…According to Koufman-Frederick et al (1999), Onifade et al (2015), andEddy Spicer andDede (2006), collaboration is a process by which people work together on an intellectual, academic, or practical endeavor. In the past, that has meant in person, by letter, or on the telephone, while electronic collaboration, on the other hand, connects individuals electronically via the Internet using tools such as mail and other teamwork collaboration (e.g., videoconferencing through services like Skype and GoToMeeting), or through access to sites on the World Wide Web (Al-khateeb, 2020;Drinka & Yen, 2003;Munkvold & Zigurs, 2007;A. Oliveira et al, 2015).…”
Section: The Concept Of Electronic Collaborationmentioning
confidence: 99%
“…Recently, in the years 2020 and 2022, higher education around the world confronted significant changes as a result of the COVID-19 pandemic and the Russia-Ukraine war, respectively [2][3][4][5][6][7][8][9][10][11]. Due to the global epidemic, the year 2020 has signaled economic and social transformations that will define the coming decade in education [12,13]. On the other hand, the war that started on the 24th of February 2022 has affected not only Ukrainian and Russian students who are studying abroad but also foreign students in Ukraine and Russia.…”
Section: Introductionmentioning
confidence: 99%
“…The Kingdom of Saudi Arabia (KSA) has already chosen the upcoming decade as the critical window for achieving Saudi Vision 2030 and the 2030 Agenda goals [13][14][15]. The vision is about transitioning the Saudi economy away from the over-reliance on oil revenues to a more balanced, investment-based model.…”
Section: Introductionmentioning
confidence: 99%